Prevalence of amyotrophic lateral sclerosis (ALS), United States, 2016. Issue 3 (3rd April 2022) - Mehta, Paul; Raymond, Jaime; Punjani, Reshma; Larson, Theodore; Bove, Frank; Kaye, Wendy; Nelson, Lorene M.; Topol, Barbara; Han, Moon; Muravov, Oleg; Genson, Corina; Davis, Bryn; et al.
Abstract: Objective: To estimate the prevalence of amyotrophic lateral sclerosis (ALS) in the United States for 2016 using data from the National ALS Registry (Registry). Established in 2009, the Registry collects data on ALS patients in the U.S. to better describe the epidemiology of ALS, examine risk factors such as environmental and occupational exposures, and characterize the demographics of those living with the disease. Methods: To identify adult prevalent cases of ALS, the Registry compiles data from three national administrative databases (maintained by the Centers for Medicare and Medicaid Services, the Veterans Health Administration, and the Veterans Benefits Administration). To ascertain cases not necessarily included in these databases and to better understand risk-factors associated with ALS and disease progression, the Registry also includes data collected from patients who voluntarily enroll via a web portal to complete online surveys. Results: In 2016, the Registry conservatively identified 16, 424 adult persons who met the Registry definition of ALS for an age-adjusted prevalence rate of 5.2 per 100, 000 U.S. population. The pattern of patient characteristics (e.g., age, sex, and race/ethnicity) has not changed from previous Registry reports. Overall, ALS was more common among whites, males, and persons aged 60–69 years. The age groups with the lowest number of ALS cases were persons aged 18–39 years. Males had a higher prevalence rate of ALS than females overall and across all data sources. Conclusions: Data collected by the National ALS Registry are being used to better describe the epidemiology and demographics of ALS in the U.S.